WORKSHOP ON POWTOON-BASED VIDEO LEARNING MEDIA IN THE TEACHERS PROFESSIONALISM IMPROVEMENT OF TK EKA KAHARAP IN SIGI, KAHAYAN TENGAH, PULANG PISAU - Orbit Thomas; Annisa Wulandari; Efriani (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
The community service aimed to provide the skills for Eka Kaharap kindergarten’s teachers in the village of Sigi in creating an exciting, creative and innovative learning media. Through appropriate media, the students have a better understanding of the subject matter. By mastering the skill, it was expected that teachers of Eka Kaharap Kindergarten would be able to create and develop Powtoon-based video media as a classroom learning tool in the future. This community service activity consisted of 2 stages, namely socialization and training. The socialization and research activities were attended by teachers of Eka Kaharap kindergarten. Moreover, a module of Poutoon application as a kindergarten learning media was used as the training material. The evaluation indicator of the activity was the ability of the trainees to design and develop Powtoon-based video learning media in accordance with the kindergarten learning subject.